Konflik Sunni-Syi’ah di Indonesia Kontemporer: Polarisasi, Diskriminasi dan Kekerasan Agama - Amal, M. Khusna; Shodiq, Ahmad Fajar (Islamika Inside: Jurnal Keislaman dan Humaniora, 2019)
Abstract: This study examines the conflict between Sunni groups and Syi'ah groups in post-New Order Indonesia. Many studies have revealed the problem of religious sectarianism conflict between the two. Some argue that conflict is triggered by differences in religious identity and theology. Others see economic and political aspects as the main factors triggering religious conflict and violence. Starting from the case of the Sunni-Syi'ah conflict in Jambesari Village (Bondowoso), this study finds an interesting finding that the conflict occurred due to sharpening religious polarization and contestation. At the same time, the infiltration of intolerant religious elites from outside the village also contributed to sharpening polarization, escalating tensions, and even triggering mass acts of violence that were suspected to have originated from Sunni groups over the Syi'ah minority group. Alienation, discrimination, dissolution of recitation, vandalism, and burning of houses belonging to Syi’ah elites are forms of violence both physically and psychologically due to the occurrence of this religious conflict.